Marshall–Olkin extended two-parameter bathtub-shaped lifetime distribution. Issue 18 (11th December 2016) - Alawadhi, Fahimah A.; Sarhan, Ammar M.; Hamilton, David C.
ABSTRACT: The Marshall–Olkin extended two-parameter bathtub distribution is introduced and its structural properties are investigated, including the compounding representation of the distribution, the shapes of the density and the hazard rate function, the moments and quantiles. Estimation of the model parameters by maximum likelihood is discussed. Applications to some real data sets which motivate the usefulness of the model are provided. Comparison between the proposed model and other commonly used distributions is performed using real data sets. A simulation study is presented to investigate the accuracy of the estimates of the model's parameters.